Beyond flavour to the gut and back. Issue 1 (December 2015) - Kadohisa, Mikiko
Abstract This paper describes how food is sensed in both the mouth where it produces food reward and pleasantness that guides food intake and is sensed in the gut where it produces satiety and conditioned effects including learned appetite and learned satiety for the food eaten. Taste and other receptors present in both the mouth and gut are involved in these effects. The signals about the presence of food in the mouth and gut are transferred by separate pathways to the brain where the satiety signals from the gut reduce the reward value and subjective pleasantness of taste and other oral sensory signals including food texture. Food flavour preferences can be associatively conditioned by pairing with food in the gut in brain regions such as the orbitofrontal cortex and amygdala. Current issues considered in this paper are how gut sensing of food influences hormone release including cholecystokinin (CCK), peptide YY (PYY), and glucagon-like peptide-1 (GLP-1); how the sensing of different nutrients in the gut may influence unconditioned satiety and conditioned preference and satiety; and how cognition may modulate the pleasantness of food and thus the control of food intake.